Pemanfaatan Algoritma C4.5 untuk Mendukung Pemilihan Konsentrasi Studi yang Tepat di Teknik Informatika - Desyanti; Rudi Faisal (Bulletin of Computer Science Research, 2024)
Choosing the right study concentration in the Informatics Engineering Study Program is crucial in supporting the success of the student's learning process and career. Currently, when choosing a contrast for the information engineering study program at Campus This research uses the C4.5 algorithm to build a decision tree to help students determine study concentration based on variables such as gender, high school major, course grades, and interests and talents. This method begins with the Knowledge Discovery in Databases (KDD) process which includes data selection, data cleaning, and transformation using a Likert scale. Data from 74 fifth semester students were analyzed to produce relevant decision rules. The implementation results show that the C4.5 algorithm is able to provide high accuracy in determining the appropriate study concentration. This system is expected to be a decision support tool for students and educational institutions in the majoring process